The International Master’s Program in Oceanography and Applications in Benin - (:unkn) unknown (My University, 2025)
The state and dynamics of the oceans and seas that surround Africa are changing at an increasing pace due to anthropogenic pressures. The livelihoods of many Africans depend on fishing and ocean-​driven monsoon rains, and some African coastlines are eroding rapidly, potentially with catastrophic results to populations and infrastructure. Yet few African scientists are prepared to engage in ocean-related research. To address this deficit, the Master’s program in Oceanography and Applications1 was launched in 2008 in Benin, targeting the West African region. This program is designed to build capacity in support of regional research programs in oceanography such as PIRATA (Prediction and Research Moored Array in the Tropical Atlantic; Bourlès et al., 2019), AMMA-EGEE (African Monsoon Multidisciplinary Analyses - Oceanic Circulation and Ocean-​Atmosphere Exchanges in the Gulf of Guinea; Redelsperger et al., 2006; Bourlès et al., 2007), and PROPAO (Regional Program of Physical Oceanography in West Africa; Sohou et al., 2020).
Keywords: African Research